Aortic Root Abscess with Aorta to Right Atrium Fistula due to Vancomycin-Intermediate Staphylococcus aureus (VISA) - Stephen J. Hankinson; Elliot A. Sultanik; Gautam V. Ramani (Case Reports in Cardiology)
We present a case of root abscess with aorta to right atrium fistula due to vancomycin-intermediate Staphylococcus aureus (VISA) after limb amputation and cardiac surgery. Patient underwent redo aortic valve replacement, patch repair of aorta to right atrial fistula, and tricuspid valve repair with a ring. Fistula formation is a rare complication of prosthetic valve endocarditis (PVE). This is the first case to discuss aortocavitary fistula (ACF) formation due to VISA. Transesophageal echocardiogram (TEE) is the preferred imaging modality to diagnose ACF.